Advanced engineering mathematics - Stroud, K.A.; Booth, Dexter J. (New York : Industrial Press Inc., 2011)
With a step-by-step programmed approach that is complemented by hundreds of worked examples and exercises, this title is suitable as an on-the-job reference for professionals or as a self-study guide for students. It contains test exercises, learning outcomes, further problems, and Can You? checklists to enhance learning and comprehension.
Numerical Solution of Equations and Interpolation. -- Laplace Transforms Part 1. -- Laplace Transforms Part 2. -- Laplace Transforms Part 3. -- Z Transforms. -- Fourier Series. -- Introduction to the Fourier Transforms. -- Power Series Solutions of Ordinary Differential Equations. -- Numerical Solutions of Ordinary Differential Equations. -- Partial Differentiation. -- Partial Differential Equations. -- Matrix Algebra. -- Numerical Solutions of Partial Differential Equations. -- Multiple Integration 1. -- Multiple Integration 2. -- Integral Functions. -- Vector Analysis 1. -- Vector Analysis 2. -- Vector Analysis 3. -- Complex Analysis 1. -- Complex Analysis 2. -- Complex Analysis 3. -- Optimization and Linear Programming. -- Appendix. -- Answers. --
Includes index.
Keywords: ENGINEERING MATHEMATICS -- PROGRAMMED INSTRUCTION